A spiro heterocyclic aromatic compound and its application

By using spiroheterocyclic aryl compounds as hole transport materials in perovskite solar cells, the problem of insufficient performance of hole transport materials in the prior art is solved, and higher photoelectric conversion efficiency and cell performance improvement are achieved.

CN117447384BActive Publication Date: 2024-12-27SICHUAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311389901.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2024-12-27
Estimated Expiration
2043-10-24

AI Technical Summary

Technical Problem

The existing hole transport materials have problems in perovskite solar cells, such as large hole injection barrier, high electron annihilation rate, large luminescence efficiency loss, and unbalanced mobility, which affect the photoelectric conversion efficiency and performance of the battery.

Method used

Using spiral heterocyclic aryl compounds as hole transport materials, its helical structure and high solubility optimize the performance of the hole transport layer. Compounds with good matching and steric hindrance are prepared by specific synthetic methods. hole transport layer of a wide bandgap perovskite solar cell.

Benefits of technology

It improves the photoelectric performance of perovskite solar cells, reduces the hysteresis effect, enhances the repetition and stability of the cells, and improves the photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117447384B_ABST
    Figure CN117447384B_ABST
Patent Text Reader

Abstract

The present invention provides a spiroheterocyclic aromatic compound and its application. The spiroheterocyclic aromatic compound has a structure as shown in Formula I. The present invention also discloses the application of the spiroheterocyclic aromatic compound in the preparation of a wide bandgap perovskite solar cell. The wide bandgap perovskite solar cell comprises an ITO conductive glass layer, a hole transport layer, a wide bandgap perovskite absorption layer, an electron transport layer and a metal electrode layer from bottom to top. The preparation method comprises: preparation of a substrate substrate; spin coating a toluene solution of the spiroheterocyclic aromatic compound; preparation of a wide bandgap perovskite absorption layer; preparation of an electron transport layer and a metal electrode layer. The spiroheterocyclic aromatic compound of the present invention has a large steric hindrance as a hole transport layer and has excellent solubility and film-forming properties; and the wide bandgap perovskite solar cell prepared with the spiroheterocyclic aromatic compound as a hole transport layer has high photoelectric conversion efficiency and excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a spiroheterocyclic aromatic compound and application thereof. Background Art

[0002] As the world's energy demand increases dramatically, in addition to the rational development and utilization of existing mineral energy, it has become a top priority to vigorously develop clean and renewable energy. Among them, inverted perovskite solar cells have the advantages of simple device structure, small hysteresis effect, and mature preparation process. The hole transport layer is an important structure, and its main function is to extract the holes generated by the perovskite layer and transfer them to the electrode. As a hole transport material, it must meet the following conditions: reducing the hole injection barrier of the device, reducing the annihilation of electrons at the anode interface, reducing the luminous efficiency loss of the light-emitting layer, and balancing the mobility of holes and electrons in the device and having good stability.

[0003] Organic small molecules, organic substances, and inorganic substances are the three most common types of hole transport materials. Among them, organic small molecule hole transport materials have the advantages of good solubility and fast dissolution in solvents and have attracted extensive attention from researchers. Summary of the invention

[0004] The problem to be solved by the present invention is to provide a spiroheterocyclic aromatic compound and its application, which is used to improve the injection and transmission of holes in perovskite solar cells and improve the photoelectric conversion efficiency and performance of perovskite solar cells.

[0005] The technical solution adopted to solve the technical problem is to provide a spiroheterocyclic aromatic compound, wherein the spiroheterocyclic aromatic compound has a structure as shown in Formula I:

[0006]

[0007] Where:

[0008] R1 to R5 are each independently a hydrogen atom, C 1-50 Substituted or unsubstituted alkyl, C 1-50 a substituted or unsubstituted aryl group, an ether group, a thioether group or a disubstituted amino group, and R1 to R5 may be the same or different substituent groups;

[0009] C 1-50 The substituted or unsubstituted alkyl group is methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, n-hexyl, cyclohexyl or n-octyl;

[0010] C 1-50The substituted or unsubstituted aryl group is an all-carbon aryl group or a heteroaryl group, and the heteroatom of the heteroaryl group is an oxygen atom, a nitrogen atom, a sulfur atom or a selenium atom; the substituent of the substituted aryl group is C 1-8 an alkane, an aryl, an ether, a thioether or a disubstituted amino group.

[0011] Preferably, C 1-50 The substituted or unsubstituted aryl group is one of the following substituents:

[0012]

[0013] Preferably, the spiro heterocyclic aromatic compound is one of the following structural formulas:

[0014]

[0015]

[0016]

[0017]

[0018]

[0019]

[0020] Preferably, the structure of the spiro heterocyclic aromatic compound is as shown in Formula II or Formula III,

[0021]

[0022] Preferably, the spiro heterocyclic aromatic compound is prepared by the following steps:

[0023] (1) Under an inert atmosphere, isotonic acid and sodium hydride are co-dissolved in a first solvent, and stirred at -10 to -20°C for 30 to 45 minutes, then 2-phenylmagnesium bromide is added dropwise to the stirred mixture and the mixture is heated to room temperature and stirred for 90 to 150 minutes, and then refluxed at 80 to 100°C overnight, and after removing the solvent, boron trifluoride etherate and a second solvent are added, and the mixture is stirred at 80 to 100°C overnight. After the reaction is completed, the mixture is separated, purified, and recrystallized to obtain a spirofluorene indole ketone compound;

[0024] (2) Under an inert atmosphere, the carbazole compound and sodium hydride are dissolved in a third solvent, stirred at -5 to 0°C for 30 to 45 minutes, and then 4-bromo-2,6-difluorobenzonitrile is added to the mixture, and the reaction is continued at -5 to 0°C for 1 to 1.5 hours, and then the temperature is raised to 120 to 150°C, and the reaction is kept at this temperature for 1.5 to 3 hours. After the reaction is completed, the mixture is filtered, recrystallized, and dried to obtain an intermediate compound;

[0025] (3) The spirofluorene indole ketone compound, the intermediate compound, the catalyst, the catalyst ligand and the base are dissolved in a fourth solvent, reacted at 120-160° C. in an inert atmosphere for 20-30 hours, and then separated, purified, recrystallized and dried to obtain the product.

[0026] More preferably, the first solvent, the second solvent, the third solvent and the fourth solvent are tetrahydrofuran, 1,2-dichloroethane, dimethylformamide and toluene respectively; the catalyst is cuprous iodide; the catalyst ligand is (1R,2R)-(-)-N,N'-dimethyl-1,2-cyclohexanediamine; and the base is anhydrous potassium carbonate.

[0027] More preferably, in step (1), the molar ratio of indigo carbide, sodium hydride, 2-phenylmagnesium bromide and boron trifluoride etherate is 1:1-2:1-1.5:10; in step (2), the molar ratio of carbazole compound, sodium hydride and 4-bromo-2,6-difluorobenzonitrile is 2-2.5:2.5-3:1; in step (3), the molar ratio of fluorenyl indole ketone compound, intermediate compound, catalyst, catalyst ligand and base is 1:1-1.5:0.1:0.2:2.

[0028] The present invention also provides the use of the above compound in preparing wide bandgap perovskite solar cells.

[0029] Preferably, the wide bandgap perovskite solar cell comprises, from bottom to top, an ITO conductive glass layer, a hole transport layer, a wide bandgap perovskite absorption layer, an electron transport layer and a metal electrode layer; the hole transport layer is made of a spiro-heterocyclic aromatic compound; the electron transport layer is made of C 60 and 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline; the material of the metal electrode layer is metal Cu; the thickness of the ITO conductive glass layer is 0.7-1.1 mm, the thickness of the hole transport layer is 5-10 nm, the thickness of the wide bandgap perovskite absorption layer is 300-400 nm, the thickness of the electron transport layer is 20-30 nm, and the thickness of the metal electrode layer is 100 nm.

[0030] Preferably, the wide bandgap perovskite solar cell is prepared by the following steps:

[0031] (1) pre-treating the ITO conductive glass to obtain a substrate;

[0032] (2) dissolving the spiroheterocyclic aromatic compound in an organic solvent, dropping the resulting solution having a concentration of 0.25 mg / mL onto a substrate, spin coating at a speed of 2500 to 3500 rpm for 15 to 25 seconds, annealing at 145 to 155° C. for 9 to 11 minutes, and cooling to obtain a substrate / hole transport layer film;

[0033] (3) dissolving CsI, FAI, PbBr2, PbI2 and Pb(SCN)2 in a mixed solvent and stirring to obtain a perovskite precursor solution; then spin coating the perovskite precursor solution on a substrate / hole transport layer film at a rotation speed of 3500-4500 rpm for 45-75 seconds, and starting to drop an anti-solvent when the spin coating lasts for 35-65 seconds, and then performing a primary annealing and a secondary annealing to obtain a substrate / hole transport layer / wide bandgap perovskite absorption layer film; C The mass ratio of sI, FAI, PbBr2, PbI2 and Pb(SCN)2 is 93-94:240-250:390-400:330-335:5-6; the mixed solvent is a mixture of dimethyl sulfoxide and dimethylformamide in a volume ratio of 1:4; the anti-solvent is anhydrous ether; the primary annealing temperature is 55-65°C, and the annealing time is 1.5-2.5min; the secondary annealing temperature is 95-105°C, and the annealing time is 9-11min;

[0034] (4) adding a post-treatment solution dropwise onto the substrate / hole transport layer / wide bandgap perovskite absorption layer film, spin coating at a speed of 2500-3500 rpm for 25-35 seconds, annealing at 95-105° C. for 4.5-5.5 minutes, and cooling to obtain a post-treated substrate / hole transport layer / wide bandgap perovskite absorption layer film; the post-treatment solution is an isopropanol solution of thiopheneethylamine chloride; the concentration of thiopheneethylamine chloride in the isopropanol solution of thiopheneethylamine chloride is 2.00 mg / mL;

[0035] (5) Using vacuum evaporation technology to deposit C 60 , 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline and metal Cu to obtain a wide-bandgap perovskite solar cell.

[0036] More preferably, step (5) comprises the following steps: transferring the post-processed substrate substrate / hole transport layer / wide bandgap perovskite absorption layer film to a vacuum thermal evaporation chamber, evacuating to 2×10 -4 Pa below, and heated to 500℃, The speed will be C 60 Deposit onto the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film, and then deposit 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline and metal Cu in sequence.

[0037] The present invention has the following beneficial effects:

[0038] (1) The spiro-heterocyclic aromatic compounds provided by the present invention have a molecular skeleton with a helical structure, which promotes the energy level of hole transfer, and the energy level matches well with the perovskite, which can effectively improve the photoelectric performance of the battery;

[0039] (2) The spiro heterocyclic aromatic compounds provided by the present invention have a twisted structure, large steric hindrance, high solubility and good film-forming properties, which are conducive to the preparation of the hole transport layer;

[0040] (3) The spiroheterocyclic aromatic compounds provided by the present invention are simple to synthesize, the raw materials are readily available, and they can be produced on a large scale;

[0041] (4) The wide bandgap perovskite solar cell preparation method provided by the present invention is simple to operate and is suitable for laboratory research on small-area perovskite solar devices. The battery device prepared by the preparation method has a small hysteresis effect and good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic diagram of the structure of a wide-bandgap perovskite solar cell.

[0043] Among them, 1. ITO conductive glass layer; 2. hole transport layer; 3. wide bandgap perovskite absorption layer; 4. electron transport layer; 5. metal electrode layer;

[0044] Figure 2 The JV curves of the perovskite solar cells prepared by spin coating the hole transport layer when the toluene solution concentration of the spiroheterocyclic aromatic compound T93 is 0.10 mg / mL, 0.25 mg / mL, 0.50 mg / mL and 1.00 mg / mL respectively;

[0045] Figure 3 The JV curves of the perovskite solar cells prepared when the hole transport layer annealing conditions are: 100°C annealing for 5 min, 150°C annealing for 5 min, 100°C annealing for 10 min and 150°C annealing for 10 min. DETAILED DESCRIPTION

[0046] The features and properties of the present invention are further described in detail below in conjunction with the examples. The reagents used in the examples are shown in Table 1. Those without material specifications or manufacturers are all conventional products that can be purchased commercially;

[0047] Table 1

[0048]

[0049] Example 1

[0050] A spiro heterocyclic aromatic compound having the structure shown in the following formula:

[0051]

[0052] The spiro heterocyclic aromatic compound T93 of this example is prepared as follows:

[0053]

[0054] (1) Synthesis of spirofluorene indole ketone compound B3: In a 250 mL dry Schlenk bottle equipped with a magnetic stirrer, indigo carmine B1 (1.47 g, 10 mmol) and ultra-dry tetrahydrofuran (40 mL) were added in sequence, the temperature was lowered to -15°C, and sodium hydride (60% dissolved in mineral oil, 0.6 g, 15 mmol, 1.5 eq.) was slowly added in batches under nitrogen protection. The Schlenk bottle was then placed at -15°C under nitrogen atmosphere and stirred for 30 min. min, then, still at this temperature, the freshly prepared 2-phenylmagnesium bromide Grignard reagent (11 mmol, 1.1 eq.) was slowly added to the Schlenk flask using a constant pressure dropping funnel. After the addition of the Grignard reagent was completed, the low-temperature reactor was automatically heated to room temperature and stirred for about two hours under a nitrogen atmosphere at room temperature, and then placed in an oil bath pot pre-heated to 90° C. to reflux overnight; after the reaction was completed, the Schlenk flask was cooled to room temperature and evaporated under reduced pressure on a rotary evaporator. The solvent was removed by distillation to obtain a crude hydroxyindole ketone intermediate, which was then directly transferred to a 250 mL dry round-bottom flask equipped with a magnetic stirrer, and an excess of boron trifluoride ether (≥4 eq.) and ultra-dry 1,2-dichloroethane (60 mL) were added in sequence. The mixture was then placed in a 90°C oil bath and stirred overnight. After the reaction was completed, the round-bottom flask was cooled to room temperature, a small amount of pure water was slowly added to quench the excess boron trifluoride, and sufficient pure water and dichloromethane were added to extract the product. The separated organic phase was back-extracted with water for 2 to 3 times, and then the aqueous phase was removed and the organic phase was combined. The organic phase was then dried over anhydrous sodium sulfate and filtered to obtain a filtrate. The solvent was removed by reduced pressure distillation using a rotary evaporator to obtain a crude product. The obtained residue was separated and purified by silica gel column chromatography (eluent: ethyl acetate / petroleum ether = 1 / 4, v / v), and finally recrystallized from petroleum ether / dichloromethane and dried in vacuo to obtain a white crystalline solid B3 (2.24 g, 7.9 mmol, yield 79%). 1 H NMR (400MHz, CDCl3): δ=9.28 (br, s, 1H), 7.84 (d, J=7.6Hz, 2H), 7.44 (td, J=7.6Hz, 0.8Hz, 2H), 7.25 (td, J=7.6Hz, 0.8Hz, 2H), 7.2 1 (td, J=8.0Hz, 1.2Hz, 1H), 7.09 (d, J=7.6Hz, 2H), 6.98 (d, J=7.6Hz, 1H), 6.89 (td, J=7.6Hz, 0.8Hz, 1H), 6.63 (d, J=7.6Hz, 1H) ppm. 13C NMR (100MHz, CDCl3): δ=179.38, 145.17, 142.34, 142.30, 131.69, 128.80, 128.18, 124.28, 123.98, 123.24, 120.70, 110.49, 64.22ppm. HRMS (ESI + ):calcd.for C 20 H 13 NO[M+H] + :284.1070, found 284.1075;

[0055]

[0056] (2) Synthesis of intermediate compound S2a: Under nitrogen protection, 3,6-di-tert-butylcarbazole (6.15 g, 22 mmol) was added to a 250 mL three-necked flask equipped with a magnetic stirrer, and then 60 mL of ultra-dry DMF was added under nitrogen atmosphere. The mixture was placed in an ice bath at 0°C and stirred to dissolve. When the temperature in the flask reached 0°C, sodium hydride (1.056 g, 60% dispersed in mineral oil, 26.4 mmol) was slowly added to the three-necked flask in batches under nitrogen protection. After the addition was completed, the mixed solution was allowed to continue to stir at 0°C for about 30 min, and then 4-bromo-2,6-difluorobenzonitrile (2 .18g, 10mmol) in DMF (20mL) solution (to avoid the super dry DMF absorbing water and affecting the reactivity, it can be prepared before adding), after the addition is completed, continue to stir at 0°C for 1 hour, (to ensure the constant temperature of the ice bath pot, add ice cubes from time to time), then heat the system to 140°C and stir for 2 hours, finally, after the reaction is completed and cooled to room temperature, the reaction mixture is slowly poured into water and filtered to obtain a white solid, first rinsed with pure water for several times, then slurried with methanol, petroleum ether and ethyl acetate for half an hour, and finally recrystallized and further dried to obtain a white powder solid S2a (6.63g, 9mmol, yield 90%); 1 H NMR (400MHz, CDCl3): δ=8.13 (d, J=1.6Hz, 4H), 7.54 (dd, J=8.8Hz, 1.6Hz, 4H), 7.36 (d, J=8.8Hz, 4H), 6.84 (s, 2H), 1.47 (s, 36H)ppm. 13 C NMR (100MHz, CDCl3): δ=151.41, 144.63, 144.26, 138.97, 131.19, 128.95, 124.56, 124.33, 116.99, 113.34, 109.40, 34.99, 32.10ppm. HRMS (ESI+ ):calcd.for C 47 H 50 79 BrN3[M+Na] + :758.3081, found 758.3078; calcd.for C 47 H 50 81 BrN3[M+Na] + :760.3060, found 760.3065;

[0057]

[0058] (3) Synthesis of spiroheterocyclic aromatic compound T93: B3 (28.3 mg, 0.1 mmol), S2a (81.1 mg, 0.11 mmol, 1.1 eq.), cuprous iodide (1.9 mg, 0.01 mmol, 10 mol%), (1R,2R)-(-)-N,N'-dimethyl-1,2-cyclohexanediamine (3.2 μL, 0.02 mmol, 20 mol%), and anhydrous potassium carbonate (27.6 mg, 0.2 mmol, 2.0 eq.) were sequentially added to a 25 mL dry Schlenk tube equipped with a magnetic stirrer. Ultra-dry 4% ethanol was added under nitrogen atmosphere. Toluene (2 mL) was added and sealed with a Teflon stopper. The Schlenk tube was then placed in an oil bath at 150° C. and stirred for 24 hours under a nitrogen atmosphere. After the reaction was completed, the Schlenk tube was cooled to room temperature and filtered with diatomaceous earth to remove the metal salt. The filtrate was subjected to reduced pressure distillation on a rotary evaporator to remove the solvent to obtain a crude product. The crude product residue was separated and purified by silica gel column chromatography (eluent: ethyl acetate / dichloromethane / petroleum ether=1 / 10 / 80, v / v / v), and finally recrystallized from petroleum ether / dichloromethane and dried in vacuo to obtain a pale yellow solid powder T93 (81.1 mg, 0.086 mmol, yield 86%). 1 H NMR (400MHz, CDCl3): δ=8.15 (s, 4H), 7.97 (s, 2H), 7.84 (d, J=7.6Hz, 2H), 7.58 (dd, J=8.4Hz, 1.6Hz, 4 H), 7.48-7.41 (m, 6H), 7.32-7.20 (m, 4H), 7.07-6.99 (m, 3H), 6.75 (d, J=7.2Hz, 1H), 1.48 (s, 36H)ppm. 13C NMR (100MHz, CDCl3): δ=175.42, 144.95, 144.45, 144.40, 142.33, 142.29, 140.71, 138.94, 131.05, 129.20, 129.08, 128.39, 1 25.10, 124.49, 124.39, 124.36, 123.87, 120.97, 116.93, 113.46, 110.23, 110.04, 109.47, 63.65, 34.98, 32.11ppm.HRMS (ESI + ):calcd.for C 67 H 62 N4O[M+Na] + :961.4816, found 961.4815.

[0059] The spiroheterocyclic aromatic compound T93 prepared in this embodiment is used in the preparation of wide-bandgap perovskite solar cells. The wide-bandgap perovskite solar cell comprises, from bottom to top, an ITO conductive glass layer with a thickness of 0.7 mm, a hole transport layer with a thickness of 7 nm, a wide-bandgap perovskite absorption layer with a thickness of 350 nm, an electron transport layer with a thickness of 25 nm, and a metal electrode layer with a thickness of 100 nm.

[0060] In this embodiment, the wide bandgap perovskite solar cell is prepared by the following steps:

[0061] (1) Set the square resistance to 10Ω·sq -1 The ITO conductive glass with an average transmittance of more than 85% is used as the base material, and ultrasonic cleaning is performed with Dikang 90 glass cleaning agent for 30 minutes, and then ultrasonic cleaning is performed with deionized water for 30 minutes and repeated 3 times, and then ethanol is used to clean in an ultrasonic machine for 30 minutes, and then taken out and blown dry with a nitrogen gun, and ultraviolet ozone cleaning is performed for 15 minutes to obtain a substrate;

[0062] (2) 80 μL of a toluene solution of a spiroheterocyclic aromatic compound T93 with a concentration of 0.25 mg / mL was added dropwise to the substrate, and the substrate was spin-coated at a speed of 3000 rpm for 20 s. After the spin coating, the substrate was placed on a hot plate at 150° C. for full annealing for 10 min and then cooled to obtain a substrate / hole transport layer film;

[0063] (3) 93.53 mg of CsI, 247.64 mg of FAI (formamidine iodide), 396.37 mg of PbBr2, 331.93 mg of PbI2 and 5.82 mg of Pb(SCN)2 were dissolved in a solvent mixed with 1200 mL of dimethylformamide and 300 mL of dimethyl sulfoxide, and stirred to obtain a perovskite precursor solution; the perovskite precursor solution was spin-coated on the substrate / hole transport layer film at a speed of 4000 rpm for 60 s, and when the spin coating reached 35 s, 620 μL of anhydrous ether was added dropwise, and after the spin coating was completed, annealing was performed at 60°C for 2 min, and then annealing was performed at 100°C for 10 min to obtain a substrate / hole transport layer / wide bandgap perovskite absorption layer film;

[0064] (4) dropping 75 μL of a 2.00 mg / mL isopropanol solution of thiopheneethylamine chloride on the substrate / hole transport layer / wide bandgap perovskite absorber film, and spin coating at 3000 rpm for 30 seconds. After the spin coating, the film was placed on a hot plate at 100° C. for annealing for 5 minutes and then cooled to obtain a post-treated substrate / hole transport layer / wide bandgap perovskite absorber film;

[0065] (5) Transfer the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film to a vacuum thermal evaporation chamber, and use a molecular pump to evacuate the evaporation chamber to a vacuum of 2×10 -4 Pa below, raise the temperature to 500℃, The speed will be C 60 Deposit onto the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film with a deposition thickness of 20 nm; after cooling, repeat the above operation to evaporate 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline with a deposition thickness of 5 nm; after cooling, evaporate the Cu electrode again to obtain a wide bandgap perovskite solar cell.

[0066] Example 2

[0067] A spiro heterocyclic aromatic compound having the structure shown in the following formula:

[0068]

[0069] The spiro heterocyclic aromatic compound T85 of this embodiment is prepared as follows:

[0070]

[0071] (1) Synthesis of spirofluorene indole ketone compound B3: In a 250 mL dry Schlenk bottle equipped with a magnetic stirrer, indigo carmine B1 (1.47 g, 10 mmol) and ultra-dry tetrahydrofuran (40 mL) were added in sequence, the temperature was lowered to -15°C, and sodium hydride (60% dissolved in mineral oil, 0.6 g, 15 mmol, 1.5 eq.) was slowly added in batches under nitrogen protection. The Schlenk bottle was then placed at -15°C under nitrogen atmosphere and stirred for 30 min. min, then, still at this temperature, the freshly prepared 2-phenylmagnesium bromide Grignard reagent (11 mmol, 1.1 eq.) was slowly added to the Schlenk flask using a constant pressure dropping funnel. After the addition of the Grignard reagent was completed, the low-temperature reactor was automatically heated to room temperature and stirred for about two hours under a nitrogen atmosphere at room temperature, and then placed in an oil bath pot pre-heated to 90° C. to reflux overnight; after the reaction was completed, the Schlenk flask was cooled to room temperature and evaporated under reduced pressure on a rotary evaporator. The solvent was removed by distillation to obtain a crude hydroxyindole ketone intermediate, which was then directly transferred to a 250 mL dry round-bottom flask equipped with a magnetic stirrer, and an excess of boron trifluoride ether (≥4 eq.) and ultra-dry 1,2-dichloroethane (60 mL) were added in sequence. The mixture was then placed in a 90°C oil bath and stirred overnight. After the reaction was completed, the round-bottom flask was cooled to room temperature, a small amount of pure water was slowly added to quench the excess boron trifluoride, and sufficient pure water and dichloromethane were added to extract the product. The separated organic phase was back-extracted with water for 2 to 3 times, and then the aqueous phase was removed and the organic phase was combined. The organic phase was then dried over anhydrous sodium sulfate and filtered to obtain a filtrate. The solvent was removed by reduced pressure distillation using a rotary evaporator to obtain a crude product. The obtained residue was separated and purified by silica gel column chromatography (eluent: ethyl acetate / petroleum ether = 1 / 4, v / v), and finally recrystallized from petroleum ether / dichloromethane and dried in vacuo to obtain a white crystalline solid B3 (2.24 g, 7.9 mmol, yield 79%).

[0072]

[0073] (2) Synthesis of intermediate compound S2b: Under nitrogen protection, 22 mmol of carbazole was added to a 250 mL three-necked flask equipped with a magnetic stirrer. Then, 60 mL of ultra-dry DMF was added under nitrogen atmosphere. The mixture was placed in an ice bath at 0°C and stirred to dissolve. When the temperature in the flask reached 0°C, sodium hydride (1.056 g, 60% dispersed in mineral oil, 26.4 mmol) was slowly added to the three-necked flask in batches under nitrogen protection. After the addition was completed, the mixed solution was allowed to continue stirring at 0°C for about 30 min. Then, 4-bromo-2,6-difluorobenzonitrile (2.18 g, 1 0mmol) DMF (20mL) solution (to avoid the super dry DMF absorbing water and affecting the reactivity, it can be prepared before adding), after the addition is completed, continue to stir at 0°C for 1 hour, (to ensure the constant temperature of the ice bath pot, add ice cubes from time to time), then heat the system to 140°C and stir for 2 hours, finally, after the reaction is completed and cooled to room temperature, the reaction mixture is slowly poured into water and filtered to obtain a white solid, first rinsed with pure water for several times, and then slurried with methanol, petroleum ether and ethyl acetate for half an hour, and finally recrystallized and further dried to obtain a white powder solid S2b (4.25g, 8.3mmol, yield 83%); 1 H NMR (400MHz, CDCl3): δ=8.16 (d, J=7.2Hz, 4H), 7.93 (s, 2H), 7.52 (td, J=8.0Hz, 1.2Hz, 4H), 7.42-7.35 (m, 8H)ppm. 13 C NMR (100MHz, CDCl3): δ=143.71, 140.41, 132.02, 129.24, 126.73, 124.41, 121.68, 120.98, 111.84, 109.81ppm. HRMS (ESI + ):calcd.forC 31 H 18 79 BrN3[M+Na] + :534.0577, found 534.0572; calcd.for C 31 H 18 81 BrN3[M+Na] + :536.0556, found 536.0556;

[0074]

[0075] (3) Synthesis of spiroheterocyclic aromatic compound T85: B3 (56.6 mg, 0.2 mmol), S2b (112.7 mg, 0.22 mmol, 1.1 eq.), cuprous iodide (3.8 mg, 0.02 mmol, 10 mol%), (1R,2R)-(-)-N,N'-dimethyl-1,2-cyclohexanediamine (6.4 μL, 0.04 mmol, 20 mol%), and anhydrous potassium carbonate (55.2 mg, 0.4 mmol, 2.0 eq.) were sequentially added to a 25 mL dry Schlenk tube equipped with a magnetic stirrer. Ultra-dry toluene (2 mL) was added and sealed with a Teflon stopper. The Schlenk tube was then placed in an oil bath at 150° C. and stirred for 24 hours under a nitrogen atmosphere. After the reaction was completed, the Schlenk tube was cooled to room temperature and filtered with diatomaceous earth to remove the metal salt. The filtrate was subjected to reduced pressure distillation on a rotary evaporator to remove the solvent to obtain a crude product. The crude residue was separated and purified by silica gel column chromatography (eluent: ethyl acetate / dichloromethane / petroleum ether=1 / 10 / 80, v / v / v), and finally recrystallized from petroleum ether / dichloromethane and dried in vacuo to obtain a white solid T85 (137.2 mg, 0.19 mmol, yield 96%). 1 H NMR (400MHz, CDCl3): δ=8.16 (d, J=7.6Hz, 4H), 8.07 (s, 2H), 7.84 (d, J=7.6Hz, 2H), 7.57-7.49 (m, 8H), 7.44 (t, J=7.6Hz, 2 H), 7.38 (t, J=6.8Hz, 4H), 7.32 (d, J=4.4Hz, 2H), 7.22 (t, J=8.0Hz, 2H), 7.05 (d, J=7.6Hz, 3H), 6.77 (d, J=7.6Hz, 1H) ppm. 13 C NMR (100MHz, CDCl3): δ=175.53, 144.88, 143.95, 142.30, 142.20, 140.96, 140.53, 131.07, 129.26, 129.13, 128.39, 126.7 8, 125.26, 125.23, 125.21, 124.42, 123.81, 121.57, 120.99, 120.92, 113.12, 110.82, 109.95, 109.92, 63.65ppm.HRMS (ESI + ):calcd.for C 51 H 30 N4O[M+H] + :715.2493, found 715.2498.

[0076] The spiroheterocyclic aromatic compound T85 prepared in this embodiment is used in the preparation of wide-bandgap perovskite solar cells. The wide-bandgap perovskite solar cells are composed of an ITO conductive glass layer with a thickness of 0.7 mm, a hole transport layer with a thickness of 7 nm, a wide-bandgap perovskite absorption layer with a thickness of 350 nm, an electron transport layer with a thickness of 25 nm, and a metal electrode layer with a thickness of 100 nm from bottom to top.

[0077] In this embodiment, the wide bandgap perovskite solar cell is prepared by the following steps:

[0078] (1) Set the square resistance to 10Ω·sq -1 The ITO conductive glass with an average transmittance of more than 85% is used as the base material, and ultrasonic cleaning is performed with Dikang 90 glass cleaning agent for 30 minutes, and then ultrasonic cleaning is performed with deionized water for 30 minutes and repeated 3 times, and then ethanol is used to clean in an ultrasonic machine for 30 minutes, and then taken out and blown dry with a nitrogen gun, and ultraviolet ozone cleaning is performed for 15 minutes to obtain a substrate;

[0079] (2) dropping 80 μL of a toluene solution of a spiroheterocyclic aromatic compound T85 with a concentration of 0.25 mg / mL onto a substrate, and spin coating it at a speed of 3000 rpm for 20 s. After the spin coating, the substrate was placed on a hot plate at 150° C. for full annealing for 10 min and then cooled to obtain a substrate / hole transport layer film;

[0080] (3) 93.53 mg of CsI, 247.64 mg of FAI, 396.37 mg of PbBr2, 331.93 mg of PbI2 and 5.82 mg of Pb(SCN)2 were dissolved in a solvent mixed with 1200 mL of dimethylformamide and 300 mL of dimethyl sulfoxide, and stirred to obtain a perovskite precursor solution; the perovskite precursor solution was spin-coated on the substrate / hole transport layer film at a speed of 4000 rpm for 60 s, and when the spin coating reached 35 s, 620 μL of anhydrous ether was added dropwise, and after the spin coating was completed, annealing was performed at 60°C for 2 min, and then annealing was performed at 100°C for 10 min to obtain a substrate / hole transport layer / wide bandgap perovskite absorption layer film;

[0081] (4) dropping 75 μL of a 2.00 mg / mL isopropanol solution of thiopheneethylamine chloride on the substrate / hole transport layer / wide bandgap perovskite absorber film, and spin coating at 3000 rpm for 30 seconds. After the spin coating, the film was placed on a hot plate at 100° C. for annealing for 5 minutes and then cooled to obtain a post-treated substrate / hole transport layer / wide bandgap perovskite absorber film;

[0082] (5) Transfer the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film to a vacuum thermal evaporation chamber, and use a molecular pump to evacuate the evaporation chamber to a vacuum of 2×10-4 Pa below, raise the temperature to 500℃, The speed will be C 60 Deposit onto the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film with a deposition thickness of 20 nm; after cooling, repeat the above operation to evaporate 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline with a deposition thickness of 5 nm; after cooling, evaporate the Cu electrode again to obtain a wide bandgap perovskite solar cell.

[0083] Example 3

[0084] A spiroheterocyclic aromatic compound T93, whose structure and preparation method are the same as those in Example 1.

[0085] The spiroheterocyclic aromatic compound T93 prepared in this embodiment is used in the preparation of wide-bandgap perovskite solar cells. The wide-bandgap perovskite solar cells are composed of, from bottom to top, an ITO conductive glass layer with a thickness of 1.1 mm, a hole transport layer with a thickness of 5 nm, a wide-bandgap perovskite absorption layer with a thickness of 300 nm, an electron transport layer with a thickness of 20 nm, and a metal electrode layer with a thickness of 100 nm.

[0086] The method for preparing the wide bandgap perovskite solar cell in this embodiment is the same as that in Embodiment 1.

[0087] Example 4

[0088] A spiroheterocyclic aromatic compound T93, whose structure and preparation method are the same as those in Example 1.

[0089] The spiroheterocyclic aromatic compound T93 prepared in this embodiment is used in the preparation of wide-bandgap perovskite solar cells. The wide-bandgap perovskite solar cells are composed of, from bottom to top, an ITO conductive glass layer with a thickness of 0.9 mm, a hole transport layer with a thickness of 10 nm, a wide-bandgap perovskite absorption layer with a thickness of 400 nm, an electron transport layer with a thickness of 30 nm, and a metal electrode layer with a thickness of 100 nm.

[0090] The method for preparing the wide bandgap perovskite solar cell in this embodiment is the same as that in Embodiment 1.

[0091] Example 5

[0092] A spiroheterocyclic aromatic compound T93, whose structure and preparation method are the same as those in Example 1.

[0093] The spiroheterocyclic aromatic compound T93 prepared in this embodiment is used in the preparation of wide-bandgap perovskite solar cells. The wide-bandgap perovskite solar cell comprises, from bottom to top, an ITO conductive glass layer with a thickness of 0.7 mm, a hole transport layer with a thickness of 7 nm, a wide-bandgap perovskite absorption layer with a thickness of 350 nm, an electron transport layer with a thickness of 25 nm, and a metal electrode layer with a thickness of 100 nm.

[0094] In this embodiment, the wide bandgap perovskite solar cell is prepared by the following steps:

[0095] (1) Set the square resistance to 10Ω·sq -1 The ITO conductive glass with an average transmittance of more than 85% is used as the base material, and ultrasonic cleaning is performed with Dikang 90 glass cleaning agent for 30 minutes, and then ultrasonic cleaning is performed with deionized water for 30 minutes and repeated 3 times, and then ethanol is used to clean in an ultrasonic machine for 30 minutes, and then taken out and blown dry with a nitrogen gun, and ultraviolet ozone cleaning is performed for 15 minutes to obtain a substrate;

[0096] (2) 80 μL of a toluene solution of a spiroheterocyclic aromatic compound T93 with a concentration of 0.25 mg / mL was added dropwise to the substrate, and the substrate was spin-coated at a speed of 2500 rpm for 25 seconds. After the spin coating, the substrate was placed on a hot plate at 150° C. for full annealing for 10 minutes and then cooled to obtain a substrate / hole transport layer film;

[0097] (3) 93.53 mg of CsI, 247.64 mg of FAI, 396.37 mg of PbBr2, 331.93 mg of PbI2 and 5.82 mg of Pb(SCN)2 were dissolved in a solvent mixed with 1200 mL of dimethylformamide and 300 mL of dimethyl sulfoxide, and stirred to obtain a perovskite precursor solution; the perovskite precursor solution was spin-coated on the substrate / hole transport layer film at a speed of 4000 rpm for 60 s, and when the spin coating reached 45 s, 620 μL of anhydrous ether was added dropwise, and after the spin coating was completed, annealing was performed at 60°C for 2 min, and then annealing was performed at 100°C for 10 min to obtain a substrate / hole transport layer / wide bandgap perovskite absorption layer film;

[0098] (4) dropping 75 μL of a 2.00 mg / mL isopropanol solution of thiopheneethylamine chloride on the substrate / hole transport layer / wide bandgap perovskite absorber film, and spin coating at 2500 rpm for 35 seconds. After the spin coating, the film was placed on a hot plate at 100° C. for annealing for 5 minutes and then cooled to obtain a post-treated substrate / hole transport layer / wide bandgap perovskite absorber film;

[0099] (5) Transfer the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film to a vacuum thermal evaporation chamber, and use a molecular pump to evacuate the evaporation chamber to a vacuum of 2×10-4 Pa below, raise the temperature to 500℃, The speed will be C 60 Deposit onto the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film with a deposition thickness of 20 nm; after cooling, repeat the above operation to evaporate 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline with a deposition thickness of 5 nm; after cooling, evaporate the Cu electrode again to obtain a wide bandgap perovskite solar cell.

[0100] Example 6

[0101] A spiroheterocyclic aromatic compound T93, whose structure and preparation method are the same as those in Example 1.

[0102] The spiroheterocyclic aromatic compound T93 prepared in this embodiment is used in the preparation of wide-bandgap perovskite solar cells. The wide-bandgap perovskite solar cell comprises, from bottom to top, an ITO conductive glass layer with a thickness of 0.7 mm, a hole transport layer with a thickness of 7 nm, a wide-bandgap perovskite absorption layer with a thickness of 350 nm, an electron transport layer with a thickness of 25 nm, and a metal electrode layer with a thickness of 100 nm.

[0103] In this embodiment, the wide bandgap perovskite solar cell is prepared by the following steps:

[0104] (1) Set the square resistance to 10Ω·sq -1 The ITO conductive glass with an average transmittance of more than 85% is used as the base material, and ultrasonic cleaning is performed with Dikang 90 glass cleaning agent for 30 minutes, and then ultrasonic cleaning is performed with deionized water for 30 minutes and repeated 3 times, and then ethanol is used to clean in an ultrasonic machine for 30 minutes, and then taken out and blown dry with a nitrogen gun, and ultraviolet ozone cleaning is performed for 15 minutes to obtain a substrate;

[0105] (2) 80 μL of a toluene solution of a spiroheterocyclic aromatic compound T93 with a concentration of 0.25 mg / mL was added dropwise to the substrate, and the substrate was spin-coated at a speed of 3500 rpm for 15 s. After the spin coating, the substrate was placed on a hot plate at 150° C. for full annealing for 10 min and then cooled to obtain a substrate / hole transport layer film;

[0106] (3) 93.53 mg of CsI, 247.64 mg of FAI, 396.37 mg of PbBr2, 331.93 mg of PbI2 and 5.82 mg of Pb(SCN)2 were dissolved in a solvent mixed with 1200 mL of dimethylformamide and 300 mL of dimethyl sulfoxide, and stirred to obtain a perovskite precursor solution; the perovskite precursor solution was spin-coated on the substrate / hole transport layer film at a speed of 4500 rpm for 45 s, and when the spin coating reached 50 s, 620 μL of anhydrous ether was added dropwise, and after the spin coating was completed, annealing was performed at 60°C for 2 min, and then annealing was performed at 100°C for 10 min to obtain a substrate / hole transport layer / wide bandgap perovskite absorption layer film;

[0107] (4) dropping 75 μL of a 2.00 mg / mL isopropanol solution of thiopheneethylamine chloride on the substrate / hole transport layer / wide bandgap perovskite absorber film, and spin coating at 3500 rpm for 25 s. After the spin coating, the film was placed on a 100° C. hot plate for full annealing for 5 min and cooled to obtain a post-treated substrate / hole transport layer / wide bandgap perovskite absorber film;

[0108] (5) Transfer the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film to a vacuum thermal evaporation chamber, and use a molecular pump to evacuate the evaporation chamber to a vacuum of 2×10 -4 Pa below, raise the temperature to 500℃, The speed will be C 60 Deposit onto the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film with a deposition thickness of 20 nm; after cooling, repeat the above operation to evaporate 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline with a deposition thickness of 5 nm; after cooling, evaporate the Cu electrode again to obtain a wide bandgap perovskite solar cell.

[0109] Comparative Example 1

[0110] A wide bandgap perovskite solar cell and a preparation process thereof. Compared with Example 1, the wide bandgap perovskite solar cell does not contain a hole transport layer, and the remaining components and the preparation process are the same as those of Example 1.

[0111] Comparative Example 2

[0112] A wide bandgap perovskite solar cell and its preparation process. Compared with Example 1, the hole transport layer is obtained by spin coating a toluene solution of a spiroheterocyclic aromatic compound T93 with a concentration of 0.10 mg / mL, and the remaining components and preparation process are the same as those in Example 1.

[0113] Comparative Example 3

[0114] A wide bandgap perovskite solar cell and its preparation process. Compared with Example 1, the hole transport layer is obtained by spin coating a toluene solution of a spiroheterocyclic aromatic compound T93 with a concentration of 0.50 mg / mL, and the remaining components and preparation process are the same as those in Example 1.

[0115] Comparative Example 4

[0116] A wide bandgap perovskite solar cell and its preparation process. Compared with Example 1, the annealing condition of the hole transport layer is: fully annealing on a hot stage at 100° C. for 5 minutes, and the other components and preparation process are the same as those in Example 1.

[0117] Comparative Example 5

[0118] A wide bandgap perovskite solar cell and its preparation process. Compared with Example 1, the annealing condition of the hole transport layer is: fully annealing on a hot stage at 150° C. for 5 minutes, and the other components and preparation process are the same as those in Example 1.

[0119] Comparative Example 6

[0120] A wide bandgap perovskite solar cell and its preparation process. Compared with Example 1, the annealing condition of the hole transport layer is: full annealing on a 100° C. hot stage for 10 minutes, and the other components and preparation process are the same as those in Example 1.

[0121] Experimental example

[0122] The performance of the wide bandgap perovskite solar cells prepared in Example 1, Example 2 and Comparative Example 1 was measured, and the results are shown in Table 1.

[0123] Table 2

[0124] project <![CDATA[V oc / V]]> <![CDATA[J SC / mA cm -2 ]]> FF / % <![CDATA[PCE max / %]]> Example 1 0.88 15.72 71.64 9.87 Example 2 0.75 14.24 63.62 6.82 Comparative Example 1 0.49 13.30 61.60 4.04

[0125] The performance of the wide bandgap perovskite solar cells prepared in Example 1 and Comparative Examples 2-3 was measured. The results are as follows: Figure 2 It can be seen that when the hole transport layer is spin-coated from a toluene solution of spiroheterocyclic aromatic compounds with a concentration of 0.25 mg / mL, the device has the maximum photoelectric conversion efficiency. Compared with the wide-bandgap perovskite solar cells without a hole transport layer, the open-circuit voltage, short-circuit current and filling factor are all improved, and the photoelectric conversion efficiency of the perovskite solar device is also significantly improved.

[0126] The performance of the wide bandgap perovskite solar cells prepared in Example 1 and Comparative Examples 4-6 was measured. The results are as follows: Figure 3 It can be seen that the wide-bandgap perovskite solar cell prepared by annealing the hole transport layer at an annealing temperature of 150°C and an annealing time of 10 min has the highest photoelectric conversion efficiency and a higher open circuit voltage.

[0127] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.

Claims

1. A spiroheterocyclic aromatic compound, characterized in that: The structure of the spiro heterocyclic aromatic compound is shown in Formula II or Formula III, 。 2. The spiro heterocyclic aromatic compound according to claim 1, characterized in that: The spiro heterocyclic aromatic compound is prepared by the following steps: (1) Under an inert atmosphere, isotonic acid and sodium hydride are co-dissolved in a first solvent, stirred at -10 to -20°C for 30 to 45 minutes, then 2-phenylmagnesium bromide is added dropwise to the stirred mixture and the mixture is heated to room temperature and stirred for 90 to 150 minutes, then refluxed at 80 to 100°C overnight, and after removing the solvent, boron trifluoride etherate and a second solvent are added, stirred at 80 to 100°C overnight, and after the reaction is completed, the mixture is separated, purified, and recrystallized to obtain a spirofluorene indole ketone compound; (2) Under an inert atmosphere, the carbazole compound and sodium hydride are co-dissolved in a third solvent, stirred at -5 to 0 °C for 30 to 45 min, and then 4-bromo-2,6-difluorobenzonitrile is added to the mixture, and the reaction is continued at -5 to 0 °C for 1 to 1.5 h, and then the temperature is raised to 120 to 150 °C, and the reaction is kept at this temperature for 1.5 to 3 h. After the reaction is completed, the mixture is filtered, recrystallized, and dried to obtain an intermediate compound; (3) dissolving the spirofluorene indole ketone compound, the intermediate compound, the catalyst, the catalyst ligand and the base in a fourth solvent, reacting at 120-160° C. in an inert atmosphere for 20-30 h, then separating, purifying, recrystallizing and drying to obtain the product; The first solvent, the second solvent, the third solvent and the fourth solvent are tetrahydrofuran, 1,2-dichloroethane, dimethylformamide and toluene respectively; the catalyst is cuprous iodide; the catalyst ligand is ( 1R , 2R )-(-)- N , N' -dimethyl-1,2-cyclohexanediamine; the base is anhydrous potassium carbonate.

3. The spiroheterocyclic aromatic compound according to claim 2, characterized in that: In the step (1), the molar ratio of indigo carbide, sodium hydride, 2-phenylmagnesium bromide and boron trifluoride etherate is 1:1-2:1-1.5:10; in the step (2), the molar ratio of the carbazole compound, sodium hydride and 4-bromo-2,6-difluorobenzonitrile is 2-2.5:2.5-3:1; in the step (3), the molar ratio of the fluorenyl indole ketone compound, the intermediate compound, the catalyst, the catalyst ligand and the base is 1:1-1.5:0.1:0.2:

2.

4. Use of the spiroheterocyclic aromatic compound according to any one of claims 1 to 3 in the preparation of wide bandgap perovskite solar cells.

5. The use according to claim 4, characterized in that The wide bandgap perovskite solar cell comprises, from bottom to top, an ITO conductive glass layer, a hole transport layer, a wide bandgap perovskite absorption layer, an electron transport layer and a metal electrode layer; the hole transport layer is made of a spiro-heterocyclic aromatic compound; the electron transport layer is made of C 60 and 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline; the material of the metal electrode layer is metal Cu; the thickness of the ITO conductive glass layer is 0.7~1.1 mm, the thickness of the hole transport layer is 5~10 nm, the thickness of the wide bandgap perovskite absorption layer is 300~400 nm, the thickness of the electron transport layer is 20~30 nm, and the thickness of the metal electrode layer is 100 nm.

6. The use according to claim 4, characterized in that The wide bandgap perovskite solar cell is prepared by the following steps: (1) pre-treating the ITO conductive glass to obtain a substrate; (2) dissolving the spiroheterocyclic aromatic compound in an organic solvent, dropping the obtained solution with a concentration of 0.25 mg / mL onto a substrate, spin coating at a speed of 2500-3500 rpm for 15-25 s, annealing at 145-155 °C for 9-11 min, and cooling to obtain a substrate / hole transport layer film; (3) dissolving CsI, FAI, PbBr2, PbI2 and Pb(SCN)2 in a mixed solvent and stirring uniformly to obtain a perovskite precursor solution; The perovskite precursor solution is then spin-coated on the substrate / hole transport layer film at a speed of 3500-4500 rpm for 45-75 s, and the anti-solvent is added dropwise at 35-50 s of spin coating, followed by primary annealing and secondary annealing to obtain a substrate / hole transport layer / wide bandgap perovskite absorption layer film; the mass ratio of CsI, FAI, PbBr2, PbI2 and Pb(SCN)2 is 93-94:240-250:390-400:330-335:5-6; the mixed solvent is a mixture of dimethyl sulfoxide and dimethylformamide in a volume ratio of 1:4; the anti-solvent is anhydrous ether; the primary annealing temperature is 55-65 °C, and the annealing time is 1.5-2.5 min; the secondary annealing temperature is 95-105 °C, and the annealing time is 9-11 min; (4) adding the post-treatment solution dropwise onto the substrate / hole transport layer / wide band gap perovskite absorption layer film, spin coating at a speed of 2500-3500 rpm for 25-35 s, annealing at 95-105 °C for 4.5-5.5 min, and cooling to obtain the post-treatment substrate / hole transport layer / wide band gap perovskite absorption layer film; The post-treatment solution is an isopropanol solution of thiopheneethylamine chloride; the concentration of thiopheneethylamine chloride in the isopropanol solution of thiopheneethylamine chloride is 2.00 mg / mL; (5) Using vacuum evaporation technology to deposit C 60 , 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline and metal Cu to obtain a wide-bandgap perovskite solar cell.

7. The use according to claim 6, characterized in that The step (5) comprises the following steps: transferring the post-processed substrate / hole transport layer / wide bandgap perovskite absorption layer film to a vacuum thermal evaporation chamber, evacuating the chamber to a vacuum of 2×10 -4 Pa and heated to 500 °C, C60 was deposited on the post-treated substrate / hole transport layer / wide bandgap perovskite absorption layer film at a rate of 0.1 Å / s, and then 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline and metal Cu were deposited in sequence.

Citation Information

Patent Citations

  • Photoelectric conversion element, imaging element, optical sensor, and compound

    CN111868951A

  • Thiophene formamidine chloride-doped high-efficiency wide-band gap perovskite solar cell and preparation method thereof

    CN114628592A

  • SPIROINDOLENONE

    DE102020007381A1

  • Spirocyclic Azaindole Derivatives

    US20090156593A1

  • Perovskite thin-film photovoltaic cell and preparation method thereof

    US20170162809A1